2023
DOI: 10.1186/s13256-023-04194-4
|View full text |Cite
|
Sign up to set email alerts
|

Durable effects of deep brain ultrasonic neuromodulation on major depression: a case report

Thomas S. Riis,
Daniel A. Feldman,
Lily C. Vonesh
et al.

Abstract: Background Severe forms of depression have been linked to hyperactivity of the subcallosal cingulate cortex. The ability to stimulate the subcallosal cingulate cortex or associated circuits noninvasively and directly would maximize the number of patients who could receive treatment. To this end, we have developed an ultrasound-based device for effective noninvasive modulation of deep brain circuits. Here we describe an application of this tool to an individual with treatment-resistant depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Further, the skull correction method used here [37] enabled a compensation for the increased attenuation of this relatively high frequency. Previous studies validated the neuromodulatory efficacy of this parameter, being appropriate to modulate fMRI blood oxygenation leveldependent activity at target and to induce mood changes in subjects with major depressive disorder [7,34]. The pulse repetition frequency and duty cycle were chosen to maximize acoustic intensity and acoustic duration to enhance efficacy [48] while minimizing heating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the skull correction method used here [37] enabled a compensation for the increased attenuation of this relatively high frequency. Previous studies validated the neuromodulatory efficacy of this parameter, being appropriate to modulate fMRI blood oxygenation leveldependent activity at target and to induce mood changes in subjects with major depressive disorder [7,34]. The pulse repetition frequency and duty cycle were chosen to maximize acoustic intensity and acoustic duration to enhance efficacy [48] while minimizing heating.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same device, we recently delivered a substantial amount of ultrasound energy, for a total duration of 50 min of stimulation, into the subgenual cingulate cortex of a subject with major depression [34]. Following this exposure, we found that the subject's depression symptoms resolved within the first day and the beneficial effects lasted for several weeks [34]. Therefore, there is evidence that the approach reported here, when delivering substantially more ultrasound energy, could also provide therapeutic benefits to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Institutional Review Board at Virginia Tech approved all experimental procedures (IRB #21-796). N=16 healthy participants (25.7 years ± 3.4 years; range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34); M/F 5/11), who met all inclusion/exclusion criteria provided written informed consent to all aspects of the study.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…LIFU has been extensively studied in small [3][4][5] and large animals [6][7][8][9] including humans [10][11][12][13]. It has been demonstrated to produce safe [14,15] and reversible inhibition and excitation [8,16] in different parts of the cortex [12,13,17] and subcortical structures [1,18] including emerging clinical applications [19][20][21][22][23]. An additional promising clinical application for LIFU is pain as demonstrated in both primates [8,24] and humans [25,26].…”
Section: Introductionmentioning
confidence: 99%